Monitoring SDG 4.7: Assessing Education for Sustainable Development in policies, curricula, training of educators and student assessment (input-indicator) - Jorrit Holst; Mandy Singer-Brodowski; Antje Brock; Gerhard de Haan (Sustainable Development, 2024)
Education is viewed as a critical keystone in achieving the Sustainable Development Goals (SDGs). Specifically, Education for Sustainable Development (ESD) is meant to enable everyone to contribute to sustainable development (SDG 4.7). This target is monitored using the global indicator 4.7.1 – mainstreaming of ESD in policies, curricula, training of educators and student assessment. Here, we offer a conceptual and methodological framework for assessments of SDG 4.7.1 (input-level) that addresses both quality and depth of implementation and speed of change. The approach combines document analysis with external expert evaluation and is applied to 10-year data (>11,000 documents) from all formal areas of education in Germany (early childhood education, school education, vocational education and training, higher education). Currently, ESD is mostly implemented in Germany as an "add-on" to the educational system, with all sub-indicators ranging from "isolated mentioning" of ESD and related concepts to "partial integration". Across most areas of education, the sub-indicator training of educators was evaluated as most deficient. With regard to the speed of change, it was found that the implementation of ESD is dynamic, with all sub-indicators having been evaluated as increasing. The proposed framework can increase the validity, reliability, and comparability of both country reporting and scientific assessments of SDG 4.7.1. We argue for independent and integrative monitoring across input, process, output and outcome to complement self-reporting and to support evidence-informed policymaking on sustainability in education.
Keywords: 330; Sustainable Development Goals (SDGs); SDG 4.7; Education for Sustainable Development (ESD); monitoring & evaluation; document analysis; input-indicator; early childhood education & school education; vocational education & higher education